In vitro evaluation of archaeosome vehicles for transdermal vaccine delivery. (2nd October 2018) - Jia, Yimei; McCluskie, Michael J.; Zhang, Dongling; Monette, Robert; Iqbal, Umar; Moreno, Maria; Sauvageau, Janelle; Williams, Dean; Deschatelets, Lise; Jakubek, Zygmunt J.; Krishnan, Lakshmi
Abstract: Archaeosomes composed of archaeal total polar lipids (TPL) or semi-synthetic analog vesicles have been used as vaccine adjuvants and delivery systems in animal models for many years. Typically administered by intramuscular or subcutaneous injections, archaeosomes can induce robust, long-lasting humoral and cell-mediated immune responses against entrapped antigens and provide protection in murine models of infectious disease and cancer. Herein, we evaluated various archaeosomes for transdermal delivery, since this route may help eliminate needle-stick injuries and needle re-use, and therefore increase patient compliance. Archaeosomes composed of TPL from different archaea ( Halobacterium salinarum, Methanobrevibacter smithii, Haloferax volcanii ) and various semi-synthetic glycolipid combinations were evaluated for their ability to diffuse across the skin barrier using an ex vivo pig skin model and the results were compared to conventional synthetic ester liposomes. Physicochemical characteristics were determined for selected formulations including vesicle size, size distribution, zeta potential, fluidity, antigen (ovalbumin) incorporation efficiency and release. Archaeosomes, in particular those composed of M. smithii TPL or the synthetic glycolipid sulfated S-lactosylarchaeol (SLA) mixed with uncharged glycolipid lactosyl archaeol (LA), appeared to be effective carriers for ovalbumin, achieving much better antigen distribution and vesicle accumulation in the skin epidermis than conventional liposomes. The enhanced skin permeation of archaeosomes may be attributed to their chemical structure and physicochemical properties such as particle size, surface charge, stability, and fluidity of their lipid bilayer.